Analisis Rasio Profitabilitas dan Rasio Likuiditas Dalam Mengukur Kinerja Keuangan PT Semen Batu Raja (Persero) Tbk Periode 2016 – 2020 Di Bursa Efek Indonesia - Erna Evriani Fitria; Deny Yudiantoro (JURNAL INOVASI SAINS TEKNOLOGI DAN BISNIS, 2022)
Financial performance is very important in determining the success of a company to generate profits. This company’s performance measurement tool uses profitability ratios including profit margin, return on assets and return on equity, and for liquidity ratios, namely the current ratio and quick ratio. The purpose of this study is to determine the level at which companies develop using the company’s financial performance profitability ratios and liquidity ratios. The analysis in this study is based on cashmere opinion, using qualitative research methods which are based on assumptions, data sets and research designs that are flexible. Sources of data obtained are secondary data and documentation with data collection techniques of observation, documents, and triangulation. Data analysis procedures using analysis of the annual financial statements of PT Semen Batu Raja Tbk. For the validity of the data the author uses triangulation and credibility. The results of the study stated that the measurement of the company’s financial performance PT Semen Batu Raja Tbk for the 2016 - 2020 period seen from the profitability ratio and liquidity ratio as well as cashmere opinion can be said to be a good company with an average calculation of financial performance for five years according to standards. The conclusion of this study is that the measurement of the financial performance of PT Semen Batu Raja (Persero) Tbk based on cashmere opinion for the 2016-2020 period can be said to be a good company because the profitability ratios and liquidity ratios from the average value of calculating five financial performance indicators for five years fulfill the value measurement standards, so that for companies to further improve service quality and increase market share.